Psychoeducation Based On Meaning Life Learning Values To Increase Students' Self-Awareness In Studying In Junior High School - Melva Syahrial; Firman; Afdal (Manajia: Journal of Education and Management, 2024)
Adolescence is a transition period full of physical, emotional and social changes. During this period, junior high school students are faced with various challenges, such as increasingly high academic demands, social pressure from peers, and the search for identity. This can cause confusion, stress, and anxiety, which can ultimately affect their learning performance. One factor that can help students face this challenge is to have good self-awareness. Self-awareness is the ability to understand oneself, including strengths and weaknesses, strengths and weaknesses, as well as values and life goals. Students with good self-awareness are better able to regulate emotions and behavior, make the right decisions. building healthy relationships with other people and setting realistic life goals and achieving them. Psychoeducation based on Meaning Life Learning (MML) values is the right solution to increase self-awareness of junior high school students. MML is an educational approach that focuses on developing meaning in life and life goals. This approach helps students to: develop an understanding of their values and beliefs. identify what is important to them in life, set realistic life goals and achieve them, increasing their resilience in facing challenges.